Answer:
a = -6
b = 1
Step-by-step explanation:
The gradient of the tangent to the curve y = ax + bx^3, will be:
dy/dx = a + 3bx²
at (2, -4)
dy/dx = a+3b(2)²
dy/dx = a+12b
Since the gradient at the point is 6, then;
a+12b = 6 ....1
Substitute x = 2 and y = -4 into the original expression
-4 = 2a + 8b
a + 4b = -2 ...2
a+12b = 6 ....1
Subtract
4b - 12b = -2-6
-8b = -8
b = -8/-8
b = 1
Substitute b = 1 into equation 1
Recall from 1 that a+12b = 6
a+12(1) = 6
a = 6 - 12
a = -6
Hence a = -6, b = 1
Hey there!
1/8(p + 24) = 9
1/8(p) + 1/8(24) = 9
1/8p + 3 = 9
SUBTRACT 3 to BOTH SIDES
1/8p + 3 - 3 = 9 - 3
CANCEL out: 3 - 3 because it gives 0
KEEP: 9 - 3 because it help solve for the p-value.
NEW EQUATION: 1/8p = 9 - 3
SIMPLIFY IT!
1/8p = 6
MULTIPLY 8 to BOTH SIDES
1/8p * 8 = 6 * 8
CANCEL out: 1/8 * 8 because it gives 1
KEEP: 6 * 8 because it gives the p-value.
NEW EQUATION: p = 6 * 8
SIMPLIFY IT!
p = 48
Therefore, your answer is: p = 48
Good luck on your assignment & enjoy your day!
~Amphitrite1040:)
Answer:
18 girls are in the group so 18:16
I think it might be rite but not to to sure